Tratamiento de aguas residuales mediante un sistema anaerobio para comunidades rurales en el sitio san josé de la parroquia bellavista. - Tinoco Sáenz, Ramiro Guillermo (2017)
This research document contains the information for the elaboration of an alternative for the treatment of wastewater through an anaerobic system for rural communities in “San José” site of the Bellavista Parish in Santa Rosa. According to the problem that exists in the site, which is, not having a wastewater treatment system in “San José” site of the Bellavista parish, contaminating the water sources by dumping the wastewater directly from the Septic tanks or other landfills. The result of this contamination has been the production of different diseases in the population such as cholera, dysentery, hepatitis A, etc. It is considered as an object of study the design of a wastewater treatment through an anaerobic system for communities with the vision that the final alternative be efficient, functional, technical and economically reliable to be able to treat wastewater produced by population of the rural communities. In order to achieve this, we first chose the site where the treatment system would be carried out, followed by a topographic survey, verifying the dimensions of San José site in Bellavista parish, then infiltration tests were carried out to determine if the soil type would be permeable or impermeable, resulting in a low permeability soil and finding the water table at 1.42 m, with the cages extracted, laboratory tests were carried out determining their SUCS classification. At the same time, for the choice of the final alternative a discard of these options was carried out at the pre-feasibility and feasibility level, taking considering the soil type and the socioeconomic position of the site, since rural communities do not have the space enough or even the economic resources for automated systems that occupy large areas of land. As a result, an alternative design of an anaerobic upflow system comprised of a grid treatment line, grease trap, septic tank and a thick upward layered filter composed of gravel in different diameters, the operation of its treatments was specified in an individual form where the technical considerations, maintenance and the results of removal based on studies and investigations are indicated. It is concluded that the anaerobic system of upward flow composed of a thick filter in ascending layers, has a great efficiency in the removal of iron, manganese, suspended solids and mesophiles. As a result an efficient system for wastewater treatment through an anaerobic system for rural communities. The construction of a wastewater treatment system at the San José site of the Bellavista parish would have favorable effects in many aspects, these being from the improvement in the health of the population to the added value of the lands. The positive effects on the health of the population are one of the greatest contributions that a project of this type can provide. In the case of people with limited resources this factor is even more important, since expenses would decrease in the purchase of medicines.